Maqashid As-Syariah Perspektif Imam Al-Ghazali; Studi Literasi Maslahah Mursalah - Abdussalam; Abdullah Shodiq (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
Throughout the history of Islamic teachings that have been brought by Rasulullah SAW since 14 centuries ago, the scholars have always placed maslahah as the main principle in Islamic sharia. Sharia's goal is to achieve maslahah. Sharia's ultimate goal is known as maqashid al-syariah. A Muslim's life will achieve worldly and ukhrawi happiness by applying the concept of maslahah, both in ijtihad and determining the value of services and goods. Modern economic theory, on the other hand, holds that the primary goal of a consumer is to obtain the greatest level of satisfaction (maximization of utility). With this goal in mind, a consumer will tend to spend his money in order to achieve the greatest level of satisfaction. As a result, there is one fundamental value contained in maximizing utility, namely the existence of an isyraf (wasteful) attitude. Despite the fact that isyraf is among the forbidden nature and satanic acts condemned by the Koran. The theme discussed in this study, which employs a descriptive qualitative methodology, is the implementation of maslahah in the opinion of Imam al-Ghazali, a prominent Islamic scholar known for his thoughts on the concept of maslahah and maqashid al-syariah. The findings show that the concept of maslahah that he proposes for human welfare can actually accommodate all human needs and is more comprehensive than the concept of utility in the modern economy.